Boosting the thermoelectric performance of GeTe by manipulating the phase transition temperature via Sb doping. Issue 20 (12th May 2021) - Jin, Yang; Wang, Dongyang; Qiu, Yuting; Zhao, Li-Dong
Abstract : With rising Sb content, the crystal symmetry of Sb-doped GeTe elevates by lowing phase transition temperature, thus leading to superior thermoelectric properties. A ZT max of ∼1.8 at 773 K and ZT ave of ∼1.1 can be obtained in Ge0.9 Sb0.1 Te. Abstract : It is well known that the thermoelectric performance of GeTe is difficult to manipulate due to its intrinsic overhigh carrier concentration and phase transition. Herein, we demonstrate that the electrical and thermal transport properties of GeTe can be synergistically promoted by lowering the phase transition temperature via doping Sb. A maximum ZT of ∼1.8 at 773 K and a ZT ave of ∼1.1 at 300–773 K are acquired in a Ge0.9 Sb0.1 Te sample. The prominently increased performance originates from three functions of the Sb dopant: (1) being an effective counter-dopant to tune the carrier concentration to an optimum range; (2) promoting the crystal symmetry of GeTe to enlarge the band degeneracy while flattening the valence band, thus elevating the density-of-state effective mass from ∼1.34 m 0 to ∼2.34 m 0 ; (3) introducing mass fluctuation and point defects to intensify phonon scattering, which decreases the lattice thermal conductivity. This work gains deep insights into the influence of Sb doping on electron–phonon transfer in GeTe-based materials, providing a valid strategy for achieving exceptional performance in other thermoelectric materials.